A STUDY IN STUNTING LOCUS VILLAGES: ANALYSIS OF DETERMINANTS ANDIMPLICATIONS FOR STUNTING IN CHILDREN UNDER FIVE - Rina Nur Hidayati; Ahmad Musadek; Faisal Ibnu (NurseLine Journal, 2025)
Background: Stunting among children under five remais a serious problem and a key target of the Sustainable Development Goals (SDGs). Understanding its determinants in stunting-locus villages is crucial for developing appropriate interventions. Objective: To analyze determinants of stunting prevalence and dominant factors influencing stunting in children under fivein stunting-locus villages. Methods: A cross-sectional correlational design. Population consisted of all children under five and their families in 13 stunting-locus villages. Sampling was conducted using a proportional cluster sampling method, involving a total of 326 participants. Bivariate analysis employed the Chi-Square test, and multivariate analysis utilized Multiple Logistic Regression. Results: There is correlation between nutritional intake (0.026), maternal education (0.037), parenting (0.035), infectious diseases (0.042) and prevalence of stunting. Nutritional intake is dominant variable influencing stunting. Meanwhile, age, gender, breastfeeding, birth weight, birth history, utilization of health facilities during pregnancy, immunization status, family income, number of family members are confounding variables. Poor nutritional intake is 14 times more likely (AOR 14.357) to result in stunted growth compared to children under five with good nutritional intake, after controlling for variables such as parenting, history of infectious diseases, maternal education. Interaction test results showed an interaction between food intake and parenting patterns (0.020) Conclusion: Efforts to address stunting should focus on improving nutritional intake for children under five, while considering quality of parenting patterns provided to them.